Prognostic value of elevated transaminase levels as predictors of adverse outcomes in patients with acute myocardial infarction - T. H. Hoang; V. V. Maiskov; I. A. Merai; Zh. D. Kobalava (Бюллетень сибирской медицины)
Aim. To assess the prevalence of elevated serum liver transaminases (LTs), including alanine aminotransferase (ALT) and aspartate aminotransferase (ALT), and their impact on in-hospital and long-term mortality in patients with acute myocardial infarction (AMI).Materials and methods. The prospective observational study included 416 consecutive AMI patients (median age 65 years, 40.9% female, 46.9% with ST elevation) without prior liver diseases, who underwent coronary angiography within 24 hours after hospitalization. AST and ALT levels were measured upon admission. LTs were considered as abnormal when their levels exceeded the local upper limit of normal. Clinical endpoints were all-cause in-hospital and 18-month mortality. Associations between clinical endpoints and various risk factors, including LT levels, were assessed by the multivariate logistic regression analysis.Results. Elevated LT levels were seen in 28.6% of AMI patients: an isolated increase in ALT was noted in 17.8% of patients, while an isolated increase in AST was registered in 25% of cases. In-hospital and 18-month mortality was 5.8 and 11.3%, respectively. Abnormal LT levels were associated with the presence of ST elevation (odds ratio (OR) 1.873, 95% confidence interval (CI) 1.218–2.881, p = 0.004), lower systolic and diastolic blood pressure (OR 0.993, 95% CI 0.986–1.0, p = 0.04 and 0.979, 95% CI 0.964–0.994, p = 0.007, respectively), higher Killip class (OR 1.510, 95% CI 1.142–1.999, p = 0.004), and higher creatinine level (OR 1.010, 95% CI 1.003–1.016, p = 0.004). In the multivariate analysis, elevated LT levels were independently associated with in-hospital and 18-month mortality (OR 3.607, 95% CI 1.199–10.848, p = 0.022 and 2.182, 95% CI 1.011–4.708, p = 0.047, respectively).Conclusion. Elevated LT levels were present in about a third of patients with AMI. They were associated with specific clinical, biological, and prognostic features, including in-hospital and long-term mortality in AMI patients.